Toxicity of Cadmium and nickel in the context of applied activated carbon biochar for improvement in soil fertility - Rahi, Ashfaq Ahmad; Younis, Uzma; Ahmed, Niaz; Ali, Muhammad Arif; Fahad, Shah; Sultan, Haider; Zarei, Tayebeh; Danish, Subhan; Taban, Süleyman; El Enshasy, Hesham Ali; Tamunaidu, Pramila; Alotaibi, Jamal M; et al. (Saudi journal of biological sciences, 2022)
Toxicity induced by heavy metals deteriorates soil fertility status. It also adversely affects the growth and yield of crops. These heavy metals become part of the food chain when crops are cultivated in areas where heavy metals are beyond threshold limits. Cadmium (Cd) and nickel (Ni) are considered the most notorious ones among different heavy metals. The high water solubility of Cd made it a potential toxin for plants and their consumers. Accumulation of Ni in plants, leaves, and fruits also deteriorates their quality and causes cancer in humans when such a Ni-contaminated diet is used regularly. Both Cd and Ni also compete with essential nutrients of plants, making the fertility status of soil poor. To overcome this problem, the use of activated carbon biochar can play a milestone role. In the recent past application of activated carbon biochar is gaining more and more attention. Biochar sorb the Cd and Ni and releases essential micronutrients that are part of its structure. Many micropores and high cation exchange capacity make it the most acceptable organic amendment to improve soil fertility and immobilize Cd and Ni. In addition to improving water and nutrients, soil better microbial proliferation enhances the soil rhizosphere ecosystem and nutrient cycling. This review has covered Cd and Ni harmful effects on crop yield and their immobilization by activated carbon biochar. The focus was made to elaborate on the positive effects of biochar on crop yield and soil health.
Keywords: Toxicity; Soil fertility; Heavy metals; Biochar; Crops yield